2018
DOI: 10.3389/fped.2018.00086
|View full text |Cite
|
Sign up to set email alerts
|

Treating Hypotension in Preterm Neonates With Vasoactive Medications

Abstract: Preterm neonates often have hypotension which may be due to various etiologies. While it is controversial to define hypotension in preterm neonates, various vasoactive medications are commonly used to provide the cardiovascular support to improve the blood pressure, cardiac output, or to treat shock. However, the literature on the systemic and regional hemodynamic effects of these antihypotensive medications in neonates is deficient and incomplete, and cautious translation of findings from other clinical popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 101 publications
(98 reference statements)
0
32
0
1
Order By: Relevance
“…Most case series in preterm and term neonates have observed that application of arginine-vasopressin is able to reverse severe hypotension without the adverse effect of hyponatremia. [3][4][5][6][7][8][9] Mild-to-moderate hyponatremia was observed in a few cases. 10,11 To our knowledge, severe hyponatremia has not been reported yet in neonates treated with arginine-vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…Most case series in preterm and term neonates have observed that application of arginine-vasopressin is able to reverse severe hypotension without the adverse effect of hyponatremia. [3][4][5][6][7][8][9] Mild-to-moderate hyponatremia was observed in a few cases. 10,11 To our knowledge, severe hyponatremia has not been reported yet in neonates treated with arginine-vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, systemic hypoxia is the leading complication associated with perinatal emergencies, contributing to the majority of neonatal deaths within the first week of life. Sustained hypoxia is also a known driver of functional alterations in the neonatal heart, resulting in contractile impairment, resistance to inotropic therapy, and end-organ perfusion defects (Miall-Allen et al , 1987; Goldstein et al , 1995; Baker et al , 2008; Joynt & Cheung, 2018a, 2018b; Carr et al , 2017; Cox et al , 2014). While until now the mechanisms have remained unclear, in this study we provide in vivo and cell-based evidence, including data from human iPSC-derived cardiomyocytes, that hypoxia-induced mitochondrial permeability transition, bioenergetic collapse, and necroinflammation contributes to neonatal cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, systemic hypoxia is the leading complication associated with perinatal emergencies, contributing to the majority of neonatal deaths within the first week of life. Sustained hypoxia is also a known driver of functional alterations in the neonatal heart, resulting in contractile impairment, resistance to inotropic therapy, and end-organ perfusion defects [61][62][63][64][65][66][67] .…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, vasopressin may also be a choice, especially as it is increasingly used in neonates for various conditions, including catecholamine and corticosteroid-resistant shock and hypotension due to ventricular outflow tract obstruction. Vasopressin also has an effect on the central nervous system, including the release of adrenocorticotropic hormones 6…”
Section: Discussionmentioning
confidence: 99%